Chongqing 2035 : A Green and Low-Carbon Growth Strategy to Decouple Economic Growth from Resource Use - World Bank (World Bank, Washington, DC, 2019)
Chongqing is at a crossroads where its GDP per capita will reach a level at which cities typically decouple economic growth from energy and resource use, as well as associated carbon emissions and pollution. However, decoupling does not happen automatically. It requires cities to adopt= green growth policies. For Chongqing to build a more innovative economy that increases its share of high-value activities, it is critical that it use resources more efficiently. Chongqing Municipality’s energy mix is dominated by coal at 60 percent and more generally by fossil fuels at 75 percent (Chongqing Municipal Bureau of Statistics and NBS Survey Office in Chongqing 2016). Moreover, an inefficient urban form and an energy- and raw material-intensive economy have led to an overconsumption of resources, serious environmental damage, and high GHG emissions. To produce one unit of GDP, Chongqing Municipality consumes 10 times more energy and emits eight times more CO2 than the Greater Tokyo Area or Seoul Capital Area. High emissions have deterioratingeffects on its environment and air quality, and they pose a significant danger to human health and risk exacerbating climate change.